Application of control-based continuation to a nonlinear structure with harmonically coupled modes. (1st April 2019) - Renson, L.; Shaw, A.D.; Barton, D.A.W.; Neild, S.A.
Highlights: First demonstration of control-based continuation on a MDOF nonlinear system. Systematic experimental characterisation of nonlinear dynamic features, including isola. Method complexity scales with instability dimension, rather than system's dimension. Control-based continuation does not necessarily require complex control strategies. Higher-harmonics in the applied force affect the system's stability properties. Abstract: This paper presents a systematic method for exploring the nonlinear dynamics of multi-degree-of-freedom (MDOF) physical experiments. To illustrate the power of this method, known as control-based continuation (CBC), it is applied to a nonlinear beam structure that exhibits a strong 3:1 modal coupling between its first two bending modes. CBC is able to extract a range of dynamical features, including an isola, directly from the experiment without recourse to model fitting or other indirect data-processing methods. Previously, CBC has only been applied to (essentially) single-degree-of-freedom (SDOF) experiments. This is the first experimental demonstration of CBC in the presence of complex MDOF response features such as internal resonance, isola, and Neimark-Sacker bifurcations. In this paper we show that the feedback-control methods and path-following techniques used in a SDOF context can equally be applied to MDOF systems. A low-level broadband excitation is initially applied to the experiment to obtain the requisite information for controller design and, subsequently, the physical experiment is treated as a "black box" that is probed using CBC. The invasiveness of the controller used is analysed and experimental results are validated with open-loop measurements. Good agreement between open- and closed-loop results is achieved, though it is found that care needs to be taken in dealing with the presence of higher-harmonics in the force applied to the structure.